Pemetaan Wakaf Produktif Masjid : Pendekatan SWOT - Junarti (ALWAQFU: Jurnal Hukum Ekonomi dan Wakaf, 2024)
This study aims to map the potential for productive waqf in the Al Hafidz Haqi School Mosque. Where the pattern of the mosque's waqf management still tends to be consumptive. Almost all waqf funds are channeled for social activities. However, if it is managed productively, the mosque's financial resources will be more independent and professional. As a vision to become a mosque that is independent and beneficial to the community. Through SWOT analysis and the IFAS-EFAS interaction method, this study determines several alternative strategies for the Al Hafidz Haqi School Mosque in empowering waqf funds, namely forming a social business-oriented mindset for mosque administrators, working with the community to establish productive businesses through the socialization of productive waqf. as well as opening up opportunities for donors from outside the foundation to provide waqf.